Pengaruh Keselamatan Kerja, Kesehatan Kerja Terhadap Produktivitas Karyawan Pada PT. Petrokopindo Cipta Selaras Gresik - Muhammad Harisuddin Barizah; Hadi Sunaryo; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe objectives of this research are: 1) to find out the description of Employee Occupational Safety and Health from employee productivity, 2) to analyze the simultaneous effect of occupational safety and health on employee productivity, 3) to analyze the effect of work safety on employee productivity, 4) to analyze the effect of occupational health on employee productivity.The sample of this study amounted to 72 respondents from 250 employees of PT Petrokopindo Cipta Selaras Gresik, sampling using proportional random sampling technique, while the data collection method in this study used a questionnaire. The data analysis method used in this research is statistical descriptive and multiple linear regression. The results of the study show that 1) occupational safety and occupational health simultaneously have a significant effect on employee productivity at PT Petrokopindo Cipta Selaras Gresik, 2) work safety has a positive and significant effect on employee productivity at PT Petrokopindo Cipta Selaras Gresik, 3) occupational health has a positive and significant effect. on the productivity of PT Petrokopindo Cipta Selaras Gresik employees. Keywords: Safety, Health, Productivity